Study guides

☆☆

Q: 6. Let j(x) = x^2 − 2x + 4. Evaluate the following.j(a) =j(3)=j(x^2) =j(x + 3) = j(x + h) =?

Write your answer...

Submit

Still have questions?

Related questions

5

104

to divide

X = 7 9x - 2x = 49

X = 7 9x - 2x = 49

X = 6 5x + 2x = 42

Evaluate the expression below when x = 2.3x2-2x+4

Let y = ln (2x), let u = 2x. Then:dy/dx = dy/du * du/dx= 1/(2x) * 2= 1/x.

Integrate by parts: ∫ uv dx = u ∫ v dx - ∫ (u' ∫ v dx) dx Let u = -2x Let v = cos 3x → u' = d/dx -2x = -2 → ∫ -2x cos 3x dx = -2x ∫ cos 3x dx - ∫ (-2 ∫ cos 3x dx) dx = -2x/3 sin 3x - ∫ -2/3 sin 3x dx = -2x/3 sin 3x - 2/9 cos 3x + c

1

Let yourself be known as x: 2x+9 = 72 2x+9 = 49 2x = 49-9 2x = 40 x = 20

It depends on the value of x. The x is a variable. To evaluate an expression, you need to have a value (number) to replace the x.

People also asked